Kampanye Stop Melawan Arus Kendaraan Melalui Media Game Telepon Cerdas - Cahyadi, Tedi Dwiki; Persada, Satria Indra Praja (Fakultas Desain Universitas Komputer Indonesia, 2023)
Traffic violation against the flow on Jl. Cihaliwung to Jl. Raya Purwakarta is very difficult to stop, even though raids are often held by the police, violations still continue to this day. Long one-way traffic forces motorists to demand efficiency for shorter travel times, so they are willing to go against the flow of the road. The large number of regional roads that are not touched by the police is also the reason for many motorists not meeting the correct driving equipment. This traffic problem which has not been resolved for more than 10 years needs to be stopped, bearing in mind that the road is often passed by large trucks and often causes traffic accidents. The suggested design solution is a traffic police simulation game, in which there is a story that contains campaign messages, a police ticketing game that can provide a police experience to players that shows how stubborn motorists are violating, and the results of the police ticketing game are also campaign messages. It is hoped that this design can make people understand the importance of obeying traffic rules, especially for teenagers and early adults.